A physicochemical assessment of the thermal stability of dextrin–colistin conjugates - Emilie Chiron (Nature Portfolio, 2021)
Abstract Attachment of polysaccharide carriers is increasingly being used to achieve precision delivery and improved effectiveness of protein and peptide drugs. Although it is clear that their clinical effectiveness relies on the purity and integrity of the conjugate in storage, as well as following administration, instability of polysaccharide-based conjugates can reduce the protective efficacy of the polymer, which may adversely affect the bioactive’s potency. As a model, these studies used dextrin–colistin conjugates, with varying degrees of polymer modification (1, 2.5 and 7.5 mol% succinoylation) to assess the effect of storage temperature (− 20, 4, 21 and 37 °C) and duration (up to 12 months) on saccharide and colistin release and antimicrobial activity. Estimation of the proportion of saccharide release (by comparison of area under the curve from size exclusion chromatograms) was more pronounced at higher temperatures (up to 3 and 35% at − 20 °C and 37 °C, respectively after 12 months), however, repeated freeze–thaw did not produce any measurable release of saccharides, while addition of amylase (20, 100, 500 IU/L) caused rapid release of saccharides (> 70% total within 24 h). At all temperatures, conjugates containing the lowest degree of succinoylation released the highest proportion of free colistin, which increased with storage temperature, however no trend in saccharide release was observed. Despite the clear physical effects of prolonged storage, antimicrobial activity of all samples was only altered after storage at 37 °C for 12 months (> threefold decreased activity). These results demonstrate significant release of saccharides from dextrin–colistin conjugates during prolonged storage in buffered solution, especially at elevated temperature, which, in most cases, did not affect antimicrobial activity. These findings provide vital information about the structure–activity relationship of dextrin–colistin conjugates, prior to full-scale commercial development, which can subsequently be applied to other polysaccharide-protein and -peptide conjugates.